2009
DOI: 10.2214/ajr.08.1895
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tumors: Optimal Cardiac MR Sequences and Spectrum of Imaging Appearances

Abstract: Recent technologic advances in cardiac MRI have resulted in the rapid acquisition of images of the heart with high spatial and temporal resolution and excellent myocardial tissue characterization. Cardiac MRI provides optimal assessment of the location, functional characteristics, and soft-tissue features of cardiac tumors, allowing accurate differentiation of benign and malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
207
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(215 citation statements)
references
References 54 publications
0
207
0
5
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Since then, many approaches have been described in the literature, such as left atriotomy, right atriotomy and biatrial approach. [11][12][13][14][15][16][17][18][19] In our series, the approaches used for left atrial myxomas are left atriotomy in 73.6% (n=145), right atriotomy in 13.7% (n=27), and biatrial approach in 12.7% patients (n=25). Based on our findings, we found that the left atriotomy approach was much more convenient, simple, rapid, and safe approach for the excision of the left atrial myxomas.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Since then, many approaches have been described in the literature, such as left atriotomy, right atriotomy and biatrial approach. [11][12][13][14][15][16][17][18][19] In our series, the approaches used for left atrial myxomas are left atriotomy in 73.6% (n=145), right atriotomy in 13.7% (n=27), and biatrial approach in 12.7% patients (n=25). Based on our findings, we found that the left atriotomy approach was much more convenient, simple, rapid, and safe approach for the excision of the left atrial myxomas.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cardiac tumours are rare (0.02-0.19%) [2][3][4]; myxoma is the commonest benign tumour in adults (45-50%) [5]. Myxomas present between the ages of 30 -70 years, and occur more frequently in women [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, thrombus does not enhance with gadolinium; however, large chronic thrombi may occasionally have peripheral enhancement, making differentiation between mass and thrombus challenging. [8] Typically, tumours demonstrate at the least partial uptake of gadolinium unless very avascular. The most common tumors metastasising to the heart are breast, kidney, oesophagus, lymphoma, leukaemia and melanoma.…”
Section: Teaching Pointmentioning
confidence: 99%